Quality Assurance System (SPMI) Management Based On E-SPMI KPIS at Widya Mandira Catholic University East Nusa Tenggara - Tangi, Hironimus; Supriyanto, Achmad (Universitas Negeri Malang, 2024)
In this article, we will review relevant literature related to SPMI management based on e-SPMI KPIs in universities, especially at Widya Mandira Catholic University. The focus of this article's study includes; a). How the implementation of e-SPMI KPIs compares to the concept of quality management in higher education, and b). Impact on institutions implementing quality assurance systems based on e-SPMI KPIs. The method of this research is to use a qualitative fan quantitative approach with a case study method. Data collection techniques through direct observation, document and archive searches, and in-depth interviews. The results of this study are The results of this study show that a). The SPMI document is determined at Unwira through the determination of key indicators based on government regulations, regulations of the PT/LAM accreditation body, based on the Vision and Strategic Plan. The Main Indicator as the key to SPMI is made in e-SPMI and developed by the Unwira IT Team. The trial of the use of e-SPMI KPIs was carried out for 3 years with achievements, namely in 2021 with a score of 2.79 out of a maximum score of 4 or 62%, in 2021 with a score of 2.5 out of a maximum score of 4 or 69.75%, and in 2023 with a score of 3.07 out of a maximum score of 4 or 76.75%. The e-SPMI KPIs model has advantages and disadvantages, so it needs continuous improvement to become a superior accredited university